1969
DOI: 10.1002/ar.1091630404
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative study of the blood vessels of the pig's skin and the influence of environmental temperature

Abstract: The vascular supply to the skin of pigs was studied in animals perfused with the dye, monastral fast blue. The arrangement of the blood vessels in control animals was in three plexuses, similar to that in other mammals but with the middle plexus poorly developed.A litter of pigs was divided into two groups at the age of 12 days and one group was raised in a warm room and the other in a cold room. The pigs were killed at age three months when the warm room was 35°C and the cold room 5°C. A quantitative evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1969
1969
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Post mortem examination.-The animals were anesthetized and the blood vascular system perfused with a dye. The results of this study have been reported elsewhere (Ingram and Weaver 1969). The thickness of the fat layer on the back was determined and the skull and limb bones were defleshed and prepared for measurement and examination.…”
Section: Methodsmentioning
confidence: 98%
“…Post mortem examination.-The animals were anesthetized and the blood vascular system perfused with a dye. The results of this study have been reported elsewhere (Ingram and Weaver 1969). The thickness of the fat layer on the back was determined and the skull and limb bones were defleshed and prepared for measurement and examination.…”
Section: Methodsmentioning
confidence: 98%
“…However, no study to date has tested this central hypothesis directly. Impairment of bone growth by disruption of blood flow is well-known (13), as are correlations of enhanced blood flow with bone elongation (14) and ear enlargement (15). It is equally well established that cold-induced vasoconstriction shunts blood away from the periphery as a heat-conserving mechanism (1, 9), just as warm temperature enhances heat dissipation via vasodilation (1).…”
mentioning
confidence: 99%
“…a rats acclimated to an ambient temperature of 6°C had a significantly greater number of blood vessels in the ears than did rats acclimated to 30°C. Ingram and Weaver (1969) reported that pigs reared a t 5°C developed more blood vessels in the skin than did animals reared a t 35°C; in a second experiment, however, Ingram and Weaver (1969) did not observe any difference in skin vascularity between animals at 20 and 35°C.…”
Section: Temperature Effectsmentioning
confidence: 91%
“…It appears that the vascularity of the skin is increased after heat or cold acclimation (Heroux, 1959;Ingram and Weaver, 1969), and there are also some observations that suggest that the number of AVAs is affected. For example, Clark and Clark (1934a) found that ears of rabbits exposed to various thermal stimuli developed more AVAs than did ears kept from such stimulation, and Morris and Bevan (1986) noted that rabbits from Vermont had more AVAs in their ears than did rabbits from warmer California.…”
Section: Introductionmentioning
confidence: 99%